CHALLENGES AND OPPORTUNITIES FOR FOOD SECURITY IN UKRAINE: INNOVATIVE PRINCIPLES OF PUBLIC POLICY AND THEIR IMPLEMENTATION IN HIGHLY COMPETITIVE CONDITIONS - TARAN, Yevhenii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article is devoted to the analysis of challenges and opportunities for food security in Ukraine in the conditions of globalization, military conflict, COVID-19 pandemic and other threats. The author examines the innovative principles of public policy that can contribute to the improvement of food security at the national and regional levels, as well as to the contribution of Ukraine to the global food security. The author uses the methods of comparative analysis, statistical analysis, case study and SWOT analysis. The author reveals that food security in Ukraine depends on many factors, such as economic development, political stability, social justice, environmental sustainability, scientific and technological progress, cultural diversity and so on. The author also identifies the main problems and risks that threaten food security in Ukraine, such as low productivity of agriculture, high dependence on import, insufficient quality and safety of food products, uneven access to resources and food, underfunding of research and innovation, corruption and inefficiency of public administration.The author proposes the innovative principles of public policy that can help solve these problems and improve the situation with food security in Ukraine. These principles include: creating a national system of monitoring and early warning of food threats, developing sustainable agricultural production, diversifying production and markets, increasing competitiveness and innovativeness of cultural and creative industries, strengthening the participation and accountability of citizens and civil society in the cultural sphere, as well as using the experience and best practices of other countries.The author develops recommendations and suggestions for the implementation of these principles of public policy in Ukraine, in particular regarding the involvement of all stakeholders, forming a strategic vision and goals, defining priorities and resources, introducing effective mechanisms of coordination and control, as well as applying modern technologies and tools for monitoring and evaluation of results.
Keywords: food security; Ukraine; innovative principles; public policy; challenges; opportunities; implementation; indicators; criteria; strategy